High-performance HV-CMOS sensors for future particle physics experiments — an overview. (20th September 2022) - Zhang, C.; Casse, G.; Franks, M.; Hammerich, J.; Karim, N.; Powell, S.; Vilella, E.; Vossebeld, J.
Abstract: HV-CMOS (High Voltage-CMOS) sensors are emerging as a prime candidate for future tracking detectors that have extreme requirements on material budget, pixel granularity, time resolution and radiation tolerance. These sensors have the advantages of full monolithic structure, low manufacture cost, fast charge collection and high radiation tolerance. Confirmed and potential tracking applications in physics experiments include the Mu3e experiment, proton EDM searches, future upgrades of LHC (Large Hadron Collider) and CEPC (Circular Electron Positron Collider). The HV-CMOS group at Liverpool is doing generic R&D to push the boundaries of HV-CMOS sensors performance, especially in terms of single point resolution, fast-timing capability and radiation tolerance. This contribution gives an overview of the latest research by the Liverpool HV-CMOS group and presents the HV-CMOS prototypes developed in Liverpool.